Pengaruh Kesehatan Mental Terhadap Hasil Belajar Peserta Didik Di SMK Negeri 3 Gunungsitoli - Kristina Laia; Justin Foera-era Lase; Hosianna Rodearni Damanik; Elizama Zebua (Departement of Mathematics Education, 2024)
This research was based on research observations during the third internship at SMK Negeri 3 Gunungsitoli, which so far was still classified as low learning outcomes influenced by the mental health of students. This research aims to determine the influence of mental health on student learning outcomes at SMK Negeri 3 Gunungsitoli. This type of research is a quantitative associative strategy method. The data collection technique instrument uses techniques in the form of open and closed questionnaire questions which are distributed to a number of respondents. The data analysis technique uses parametric statistical methods with the help of the SPSS v program. 25 for windows, with a total sample of 32 students being research subjects carried out randomly using a simple purposive sampling sampling. Knowing that the influence of the mental health variable (X) on the learning outcomes variable (Y) is 45.3%. We can see from SPSS data analysis that mental health has an influence on student learning outcomes, and vice versa, the higher the student learning outcomes, the better the mental well-being of students. compared to individuals who have low/poor mental health or have no motivation at all to achieve more optimal academic achievement